Pengaruh Proses Produksi dan Pengendalian Mutu terhadap Kualitas Produk Kain Brukat - Aprilianti, Puspa; Djachrab, Ida Rapida (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
Based on the results of observations and interviews, the background of this research is the fluctuation of production targets, actual production not meeting the targets, and defective products exceeding 3%. It is suspected that this is related to the production process and quality control not functioning properly. The research object is the embroidery department employees at PT Wiratama Prima Textile Indo Rancaekek. The type of research is associative quantitative. The primary data is in the form of questionnaires, while supporting data are collected through observation, interviews, and literature study. The population consists of all production employees in the embroidery section at PT Wiratama Prima Textile Indo Rancaekek, totaling 54 people. Based on Slovin's formula, a sample of 47 people was obtained. Respondents were determined using accidental sampling. Data testing was conducted using statistics, where previously the data were tested through validity, reliability, and normality tests. Subsequently, determination analysis, multiple correlation, and multiple regression were conducted. The results of the study showed that the reliability test results indicated that all research instruments were declared reliable, with a Cronbach’s Alpha value of 0.718 for the production process variable (X1) and 0.719 for quality control (X2), which means they fall into the high category. Partially, the production process affects 40.5% of product quality. Quality control affects 26.7% of product quality. Simultaneously, the production process and quality control affect 43.9% of product quality. The correlation coefficient (R) value of 0.662 indicates that there is a strong relationship between the two independent variables and the dependent variable.